K-19 [videorecording (DVD)] : the widowmaker - Bigelow, Kathryn; Ford, Harrison, 1942-; Neeson, Liam; Sarsgaard, Peter (Paramount Pictures, 2002)
Captain Vostrikov, a Russian naval officer has being given command of the Soviet Union's first nuclear missile submarine, K-19, at the height of the Cold War in 1961. The vessel's executive officer Captain Polenin asserts that the flagship is not yet ready for deployment. But, political pressure forces Vostrikov to sail his crew into the North Atlantic anyway, for a missile fire test that serves as a warning to the U.S. The test is a success, but a leak in the K-19's cooling system soon threatens the nuclear payload.